كيف وصلت إلينا الكتابة العربية - البكوش مفتاح محمد محمد عمر (Sharwes Scientific Journal, 2024)
Arabic writing passed through many eras of time, extending from the pre-Islamic era through the era of early Islam, to the era of prosperity in the Umayyad and Abbasid states. Writing in the first era was limited to writing the Holy Qur’an, and the scribes and writers of revelation were famous in that time, and writing was done on skins and stones, as well as the shoulders of camels The Arabs had a fair amount of knowledge, and although the Arabs of pre-Islamic times were not people of writing, writing did not spread among them except with the call of Islam, writing among them was rare, and some of them tended to memorize, because the Messenger, peace and blessings be upon him, said, “Do not write anything about me except the Qur’an.” In pre-Islamic times, poets used to write down their poems on stones and clay tablets, and writing was known in pre-Islamic times. The Holy Qur’an came to imitate the Arabs with what they understood, so it mentioned the pen, the book, and the tablets. Writing received great attention under Islam, as it was a fundamental pillar of Islamic advocacy and an important means of preserving revelation and calling for the unity of God. The Holy Qur’an glorified its status, raising its status, and thus Islamic writing and culture spread.